Reviewing the viability of renewable energy in community electrification: The case of remote Western Australian communities - Byrnes, Liam; Brown, Colin; Wagner, Liam; Foster, John (Renewable & sustainable energy reviews, 2016)
Governments and network utilities are grappling with how to manage increasing costs of electricity supply, the prospect of distributed generation while still meeting social objectives of access and affordability in remote areas. Due to geographical isolation and dispersed populations, remote Australian communities are generally electrified by distributed networks using diesel generation. This is expensive, environmentally damaging and fails to exploit vast renewable resources available. These communities are often regarded as “low hanging fruit” from a renewable energy deployment perspective. This paper examines why that fruit has not been readily picked in Australia in the context of a case study of three remote West Australian communities. In Western Australia, the local electricity distribution network service provider (DNSP) responsible for regional networks, developed a scheme (the Scheme) to incentivise renewable energy deployment in remote communities. This scheme aims to encourage communities to install renewable energy from the “bottom up” by providing a feed-in tariff capped at $0.50/kWh, to reduce the supply cost and environmental damage from diesel generation. However, to date there has been limited deployment of renewable energy in remote communities. The scheme and viability of renewable energy is assessed for three indigenous communities located in the Kimberley region of Western Australia. These communities are connected to isolated, diesel powered networks. Viability is assessed from the DNSP and community perspectives and incorporates quantitative and qualitative financial, social / human and institutional factors. Renewable energy deployment is found to benefit the DNSP and can also benefit communities subject to their cost of capital and to the imposition of connection charges. However a range of barriers are currently frustrating deployment and a dynamic and adaptive approach that recognises local challenges and provides the communities with a pathway to installation is needed.